Diplomacy of Jung Bahadur Rana: A Strategic Adaptation in 19th Century Nepal (Voice of History, 2025)
Jung Bahadur Rana, a key figure in Nepalese history, is known for establishing the Rana autocracy following the Kot Massacre of 1846. However, his significant role in shaping Nepal’s diplomatic orientation during a period of colonial expansion in South Asia remains insufficiently explored. This paper critically examines the diplomacy of Jung Bahadur Rana with a focus on the 19th-century geopolitical landscape dominated by British India and Qing China. Through a deep analysis, this study evaluates how Jung Bahadur navigated foreign threats while consolidating Nepalese sovereignty. Applying historical-interpretive methodology, this research draws from published memoirs and secondary literature. This study shows that Jung Bahadur grounded his foreign policy in pragmatism, allying with the British militarily while keeping limited but careful ties with China. The study concludes that his approach laid a durable foundation for Nepal's modern foreign policy, emphasizing neutrality, survival diplomacy, and pragmatism. By reassessing Jung Bahadur’s diplomacy, this paper contributes to the historiography of Nepal and sheds light on the long-term consequences in Nepal’s international relations.